THE WORLD HEALTH ORGANIZATION – THE (UN)ATTAINABLE IDEAL? - Blešić, Jovana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The World Health Organization is one of the UN specialized agencies. Its work and functions gained even more importance in 2020 with the emergence of the corona virus. The eyes of the entire international community focused on this organization and its Director General. Today, various criticisms may be heard when it comes to its efficiency. In this paper, the author will first present the organization itself and its significance. Then, the actions of the WHO during the pandemic will be pointed out, through the clarification of the concept of public health emergency of international concern and the use of International Health Regulations and, finally, the possible reform of this body will be discussed. The aim of this paper is to get the readers familiar with the World Health Organization and put it in the context of the year behind us and the current year.
Keywords: World Health Organization; corona virus; reform; public health emergency of international concern; International Health Regulations